TOTAL FENOLIK, FLAVONOID, DAN AKTIVITAS ANTIOKSIDAN PRODUK TEH HIJAU DAN TEH HITAM TANAMAN BANGUN-BANGUN (Coleus amboinicus) DENGAN PERLAKUAN ETT REMPAH-REMPAH - Restauli Br Siburian; Christine Jose; Ganis Fia Kartika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Coleus  amboinicus  is a plant with good antioxidant content . Antioxidants are very important  in preventing various diseases caused by free radicals.   The high antioxidant content of plant  C. amboinicus  potentially  used as raw material for making herbal tea products, such as  green tea and black tea. The objective of this research was to analyze the  total phenolics, flavonoids and antioxidant activity of green tea and black tea prepared from  C. amboinicus  plants with two different treatment, fermented plant extract (FPE) spice and control (water).  The results showed that the total phenolic and flavonoid content  of each  treatment  was different. The total phenolic content of control treatment and FPE spice green tea and black tea products  were  16,660 ± 0.251 mg AGE/g DW; 10.510 ± 0.737 mg AGE/g DW and 14,219 ± 0,198 mg AGE/g DW; 8.062 ± 0.334 mg AGE / g DW. Were  the total flavonoids treatment control and FPE spice green tea and black tea is 3.522 ± 0.077 mg CTE/g DW; 2.141 ± 0.104  mg CTE/g DW and 2.278 ± 0.057 mg CTE/g DW; 2.077 ± 0.044 mg CTE/g DW.  The content  of antioxidant activity by FTC method is highest shown  in the control treatme nt compared with ETT RR good green tea products and  black tea.  It can be concluded that green tea product of  C. amboinicus  is better  source of flavonoids, phenolics and antioxidant activity compared with the black tea product.